The Tear Osmolarity Changes After Cataract Surgery - Banu Öncel; Eylem Pınarcı; Yonca A. Akova (Türk Oftalmoloji Dergisi)
Pur po se: To determine the tear osmolarity changes in patients who had undergone phacoemulsification surgery. Ma te ri al and Met hod: Tear osmolarity measurements were performed in 30 eyes of 30 patients who had undergone cataract surgery without any complication. Measurements were performed before surgery and consecutively at 1st month, 3rd month, and 6th month after the surgery. TearLab osmometer (TearLab Corporation, San Diego, CA, USA) device was used for the measurements and paired ttest was used for statistical analysis. Re sults: The mean age of the patients was 72.3±3.7 (67-78) years. Thirteen patients were men and 17 patients were women. The mean osmolarity values were 305.8±6.5 mOsm/L before the surgery and 312.3±6.4 mOsm/L at 1st month, 307.5±5.1 mOsm/L at 3rd month and 305.1±5.7 at 6th month after the surgery. The difference between the values before surgery and at 1st month was found statistically significant (p=0.001). Dis cus si on: The tear osmolarity increases at the first month after surgery but decreases to the levels measured before surgery at the 3rd month. The increase at the first month may be due to the corneal incisions and medication used after the surgery. We think that we have to take into account this similarity increase in all cataract patients, especially in those who also have dry eye disease. (Turk J Ophthalmol 2012; 42: 35-7)